Achieving maternal and child access to essential vaccines in sub-Saharan Africa: An assessment of the dimensions of access to essential vaccines in Nigeria - Dauda John Duguru (2019)
Introduction: One of the ways of reducing unnecessary expenditure on healthcare caused by communicable diseases, is by reducing the vulnerability of the population to infectious diseases. Several studies have found vaccines to be cost effective, but to ensure that vaccines get to the populations that need them, it will be necessary to understand the factors (dimensions) that determine access to essential vaccines. Objective: This project seeks to evaluate maternal and child access to essential vaccines in terms of the dimensions of access. The aim is to identify the dimensions (dimensions of access) that affect mother and child access to essential vaccines in Nigeria, and how these factors play role in vaccine uptake. The findings from this project will give us better understanding of the determinants of access to essential vaccines and how they interrelate. Method: The research method is systematic review of literature, it includes studies that primarily explored the different dimensions of access. The findings from the systematic review were further complemented using semi structured interviews with healthcare professionals. Results: The identified dimensions of access include; availability and accommodation, effectiveness, approachability (of health facility and workers), acceptability (of vaccines and services), affordability, appropriateness or relevance, physical accessibility and information/communication. Information/communication was found to have the highest impact on access, followed by acceptability. Irrespective of availability and effectiveness of the vaccines, the acceptability of the vaccines may be poor, due to lack of “trust” and proper information. The identified dimensions of access alone, do not clearly explain the dynamics surrounding access to essential vaccines, instead “the people’s ability to interact with the dimensions of access” also play a vital role. Other factors were also identified to influence access, and they include; insecurity, trust, sociocultural factors, quality of care, safety of vaccine, prioritization and vaccine hesitancy. Conclusion: The problems of vaccine access in Nigeria vary from one region to the other, but in all of the regions, the dimensions of access found to have the most impact on vaccine uptake were; information/communication. To ensure effective vaccine access in Nigeria, a continuous system of communicating the health and economic value of vaccines should be encouraged, as opposed to occasional immunization programs. These interventions should not be directed at care givers alone, but should include community leaders, religious leaders and the youth, thereby promoting trust and acceptability of vaccines and services.